Regulations for Cancellation of a Will with the Existence of Legal Heir Based on Decision Number: 805/PDT/2018/PT.DKI - Sepwira Drana Wasistha Putra; Zainul Daulay; Muhammad Hasbi (jurnal.unprimdn.ac.id, 2026)
A will deed is an authentic deed made before a Notary pursuant to Article 15(1) of Law No. 30/2004 on the Notary Profession (amended by Law No. 2/2014). Although a notarial will carries perfect evidentiary power, it may be cancelled when it conflicts with the rights of legitimate heirs (legitieme portie). This normative juridical study employs statutory and case approaches to examine: (1) the regulatory framework for cancellation of a will in the presence of legitimate heirs; (2) the judicial considerations in High Court Decision No. 805/PDT/2018/PT.DKI; and (3) the legal consequences of that cancellation for all parties. Results show that cancellation is governed by Articles 875–940 of the Civil Code; the High Court confirmed that Will Deed No. 32 violated the heirs’ absolute share, rendering it without binding legal force; and the consequences include loss of the deed’s evidentiary power, redistribution of the estate to lawful heirs, and potential civil liability for the Notary.